Tourism and the demonstration effect: Empirical evidence - J. Carlos Monterrubio; M. Marivel Mendoza-Ontiveros (Tourism & Management Studies)
The demonstration effect has become a well-established concept in the literature on tourism. It has been commonly reported as a consequence of tourism, focusing on the emulation of tourists’ consumption patterns. However, there is very limited empirical evidence specifically focused on how tourist behaviour is actually or potentially emulated by locals. This study aims to fill this gap by presenting the findings of a research project looking at how women in a tourism destination in Mexico have adopted tourists’ behavioural patterns either entirely or partially. Based on in-depth interviews and focus groups, this study reveals that tourist behaviours, attitudes, and certain ways of thinking can be and have been actually adopted by local women. Nevertheless, it also shows that local social groups do not copy tourist behaviour blindly; instead, residents are also critical in demonstration effect processes. They observe, analyse, compare, evaluate and decide on what and how tourists’ specific behaviours are adopted.